Phosphatase and tensin homolog (PTEN) expression on oncologic outcome in renal cell carcinoma: A systematic review and meta-analysis. - Lu Tang; Xintao Li; Yu Gao; Luyao Chen; Liangyou Gu; Jianwen Chen; Xiangjun Lyu; Yu Zhang; Xu Zhang (PLoS ONE)
The phosphatase and tensin homolog (PTEN) gene is suggested to be a dormant tumor suppressor. However, the prognostic value of the loss of PTEN expression in renal cell carcinoma (RCC) remains controversial. Therefore, we conducted a meta-analysis to evaluate the association of PTEN expression with the clinicopathological presentations and outcomes of patients with RCC through immunohistochemistry staining analysis. We systematically searched for relevant studies in PubMed, Web of Science, and Embase until March 2016. Data regarding clinical stage, pathological type, Fuhrman grade, overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS) was analyzed in the present study. In total, there were 12 studies with 2,368 patients included in this meta-analysis. The low PTEN expression in RCC was significantly associated with unfavorable DSS (HR = 1.568, 95% CI 1.015-2.242) in a random-effects model but not with OS (HR = 1.046, 95% CI 0.93-1.176) and PFS (HR = 1.244, 95% CI 0.907-1.704). Other results indicated that PTEN expression was not correlated with clinical stage, pathological type, and Fuhrman grade. This meta-analysis suggests that PTEN expression is of limited value in predicting the prognosis of patients with RCC for OS and PFS via immunohistochemistry staining analysis; and that for DSS, low PTEN expression is significantly associated with an unfavorable outcome.